2014
DOI: 10.1177/0093854814553097
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism, Low Self-Control, and Violence Among a Nationally Representative Sample

Abstract: A growing body of evidence has highlighted the relationship between narcissism and violence. Importantly, however, the predominance of this evidence comes from experimental tests or small-scale samples that most often overlook the contribution of low self-control to explicating the relationship. The present study refers to the National Epidemiological Study of Alcohol and Related Conditions (NESARC) to assess narcissism, low self-control, and violence among a nationally representative sample. Using Latent Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 62 publications
3
34
0
Order By: Relevance
“…Like psychopathy, narcissism is considered a predictor of violence and aggression and is, therefore, an important personality construct to be addressed in forensic contexts (Kohut, ; Larson, Vaughn, Salas‐Wright, & Delisi, ). Nevertheless, because personality traits are dimensional by nature, the continuum of narcissism includes varying degrees of manifestations of narcissistic features and, in fact, includes varying degrees of adaptive and maladaptive forms of narcissism.…”
Section: Introductionmentioning
confidence: 99%
“…Like psychopathy, narcissism is considered a predictor of violence and aggression and is, therefore, an important personality construct to be addressed in forensic contexts (Kohut, ; Larson, Vaughn, Salas‐Wright, & Delisi, ). Nevertheless, because personality traits are dimensional by nature, the continuum of narcissism includes varying degrees of manifestations of narcissistic features and, in fact, includes varying degrees of adaptive and maladaptive forms of narcissism.…”
Section: Introductionmentioning
confidence: 99%
“…Narcissism has both grandiose manifestations (such as boastful, aggressive behavior) and vulnerable manifestations (such as a fear of being evaluated negatively; Krizan & Herlache, ; Pincus & Lukowitsky, ). Even in its subclinical form, narcissism predicts maladjustment ranging from aggression and violence to addiction and depression (Carter, Johnson, Exline, Post, & Pagano, ; Dawood & Pincus, ; Larson, Vaughn, Salas‐Wright, & Delisi, ; Rasmussen, ). In its extreme form, narcissism can develop into narcissistic personality disorder, marked by “a pervasive pattern of grandiosity (in fantasy or behavior), need for admiration, and lack of empathy” (American Psychiatric Association, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that children and adolescents low in trait self‐control exhibit greater aggressive and delinquent behaviors (Krueger, Caspi, Moffitt, White, & Stouthamer‐Loeber, ; Murphy & Eisenberg, ). Likewise, adults low in trait self‐control respond to anger‐provoking situations more aggressively (Hofmann et al, ; Jensen‐Campbell, Knack, Waldrip, & Campbell, ; Kashdan, Goodman, Mallar, & DeWall, ; Tangney et al, ) and are more likely to engage in acts of violence (e.g., pushing and hitting; Larson, Vaughn, Salas‐Wright, & Delisi, ) than are those high in this trait. Furthermore, a study on jail inmates found that those low in trait self‐control were higher in verbal and physical aggression than were inmates high in self‐control (Malouf et al, ).…”
Section: The Role Of Self‐control Across the Seven Temptation Domainsmentioning
confidence: 99%
“…Furthermore, a study on jail inmates found that those low in trait self‐control were higher in verbal and physical aggression than were inmates high in self‐control (Malouf et al, ). Finally, among people who are currently in a romantic relationship, those low in trait self‐control exhibit greater aggression toward their partner during a conflict (Finkel, DeWall, Slotter, Oaten, & Foshee, ; Larson et al, ) and are less willing to accommodate and forgive their partner's transgressions (Finkel & Campbell, ) than their high counterparts.…”
Section: The Role Of Self‐control Across the Seven Temptation Domainsmentioning
confidence: 99%